(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
A major challenge in formulating plant-based cheese lies in achieving the springiness and meltability of dairy cheese, and starch shows promise in fulfilling these textural roles. However, the functional properties of starch are mainly determined by its amylose and amylopectin content. This study aimed to determine the effect of rice starch with different levels of amylose content on the proximate, textural, and thermal properties of palm milk-based cheese analogue (PMCA). Palm milk was the main ingredient in the production of PMCA as a milk fat replacement, with chickpea flour as the source of protein. A total of 4 samples were produced with 0% starch as negative control (Sample A), 2% medium-amylose rice starch (B), 2% low-amylose rice starch (C), and 2% corn starch as positive control (D). Sample C exhibited significantly higher hardness and springiness while reduced melt ability as compared to Sample B and D. The PMCA had considerably high protein (9-14%) as compared to the literature (0.11-3.00%) and low fat (12-15%) content, that suggested chickpea flour and palm milk be considered as primary ingredients in high-protein with low-fat cheese analogue. Sample C demonstrated significantly higher (p<0.05) hardness and springiness with smaller specimen expansion in meltability as compared to samples B and D, supported by the analysis of scanning electron microscopy. In conclusion, low-amylose rice starch showed a better choice to be applied in plant-based cheese products to obtain mimicked textural characteristics with dairy cheese.